Матеріали до "Словника римового гнізда лексеми Україна" - Мовчун Л. (Лексикографічний бюлетень, 2015)
The Dictionary contains rhyme pairs and rhyme chains selected out of the Ukrainian poetic texts. It addresses to the linguists, its purpose is to fix the lexical composition of rhyme nest with the main component “Ukraine”. The dictionary may be used for the phonological, grammatical, lexical, semantic, stylistic and quantitative study of the Ukrainian rhyme.